Strain dependence of diet‐induced NASH and liver fibrosis in obese mice is linked to diabetes and inflammatory phenotype. (25th October 2013) - Farrell, Geoffrey C.; Mridha, Auvro R.; Yeh, Matthew M.; Arsov, Todor; Van Rooyen, Derrick M.; Brooling, John; Nguyen, Tori; Heydet, Deborah; Delghingaro‐Augusto, Viviane; Nolan, Christopher J.; Shackel, Nicholas A.; McLennan, Susan V.; et al.
Abstract Background & Aims Obese Alms1 mutant (foz/foz) NOD.B10 mice develop diabetes and fibrotic NASH when fed high‐fat(HF) diet. To establish whether diabetes or obesity is more closely associated with NASH fibrosis, we compared diabetic foz/foz C57BL6/J with non‐diabetic foz/foz BALB/c mice. We also determined hepatic cytokines, growth factors and related profibrotic pathways. Methods Male and female foz/foz BALB/c and C57BL6/J mice were fed HF or chow for 24 weeks before determining metabolic indices, liver injury, cytokines, growth factors, pathology/fibrosis and matrix deposition pathways. Results All foz/foz mice were obese. Hepatomegaly, hyperinsulinemia, hyperglycaemia and hypoadiponectinaemia occurred only in foz/foz C57BL6/J mice, whereas foz/foz BALB/c formed more adipose. Serum ALT, steatosis, ballooning, liver inflammation and NAFLD activity score were worse in C57BL6/J mice. In HF‐fed mice, fibrosis was severe in foz/foz C57BL6/J, appreciable in WT C57BL6/J, but absent in foz/foz BALB/c mice. Hepatic mRNA expression of TNF‐α, IL‐12, IL‐4, IL‐10 was increased (but not IFN‐γ, IL‐1β, IL‐17A), and IL‐4:IFN‐γ ratio (indicating Th‐2 predominance) was higher in HF‐fed foz/foz C57BL6/J than BALB/c mice. In livers of HF‐fed foz/foz C57BL6/J mice, TGF‐β was unaltered but PDGFα and CTGF were increased in association with enhanced α‐SMA, CD147and MMP activity. Conclusions In mice with equivalent genetic/dietary obesity, NASH development is linked to strain differences in hyperinsulinaemia and hyperglycaemia inversely related to lipid partitioning between adipose and liver. Diabetes‐mediated CTGF‐regulation of MMPs as well as cytokines/growth factors (Th‐2 cytokine predominant, PDGFα, not TGF‐β) mobilized in the resultant hepatic necroinflammatory change may contribute to strain differences in NASH fibrosis.